Eksistensi Hukum Islam Di Indonesia (Analisis Kontribusi dan Pembaruan Hukum Islam Pra dan Pasca Kemerdekaan Republik Indonesia) - Dahlia Haliah Ma'u (IAIN Manado, 2017)
The implementation of Islamic law in Indonesia is closely related to the early arrival of Islam in Indonesia. It means that after the entry of Islamic into Indonesia, Islamic law has been followed and executed by the followers of Islam in archipelago. The existence of Islamic law that is lives in the society is recognized by the Dutch Colonial. The Dutch government realized that Islamic law is one of the pillars of power that can fight against on Dutch policy. On this basis, the Dutch changed their policy by stipulating that Islamic law applies if it has been adopted by common law. The struggle of Islamic law of Indonesia to change these policies to obtain that common law is not in accordance with Islamic law will not be applied or refused by Muslim. Furthermore, post-independence, the existence of Islamic law is progressing. This is marked by the enactment of legal product by the government and has become a positive law in Indonesia.